The Potential of Probiotic Role in Tuberculosis Therapy : A Narrative Review - Fitriani, Victoria yulita; Suprapti, Budi; Amin, Muhammad (Indonesian Journal of Pharmaceutical Science and Technology, 2024)
Tuberculosis is an infectious disease that is a leading cause of death globally, as well as one of the top ten causes of death from a single infectious agent. Antibiotics treatment for tuberculosis reduces pro-inflammatory cytokines, which is one of the reasons for dysbiosis. The proportion of Actinobacteria, Firmicutes, and Bacteroidetes in the gut microbiota distinguishes between drug-sensitive and drug-resistant tuberculosis. The gut–lung axis theory explains how tuberculosis alters the gut microbiota while also altering the immune response. Probiotics have immunostimulatory and immunoregulatory properties that affect the immune system. The gut-lung axis is a two-way system that enables microbial products, endotoxins, metabolites, hormones, and cytokines to reach the bloodstream that connects the intestines and lungs, where they exert effects on both. According to the gut–lung axis theory, probiotics may play a role in tuberculosis immune responses. This review includes studies conducted in English and Indonesian from 2010-2022. The Cochrane Library, Scopus, Medline, PubMed, and grey literature databases will be used in the review. Studies that use specimens from pulmonary tuberculosis patients, healthy volunteers induced by Mycobacterium tuberculosis, volunteers with a history of pulmonary tuberculosis disease, and volunteers who had close contact with pulmonary tuberculosis patients were considered eligible. The current review highlights the immune modulation induced by probiotics usage in tuberculosis. Accordingly, probiotics have been shown to enhance the immune response against tuberculosis. More studies are needed to understand probiotic’s role in different types of tuberculosis, and the influence of different probiotic bacteria on immune modulation.